Multi-level Utility Mining: Retrieval of High Utility Itemsets in a Transaction Database. (June 2019) - Sivamathi, C; Vijayarani, S
Abstract: Utility mining is a key field in data mining, meant to reveal high utility itemsets (HUIs). It retrieves HUIs from a multi-level dataset. An algorithm MUMA (multilevel utility mining algorithm) was proposed to retrieve HUIs in a multi-level dataset. MUM algorithm implements a tree structure, called MUMT (multilevel utility mining tree), to store utility information of the itemsets. Several enhanced tree-based algorithms namely multi-level utility mining using enumeration tree (MU_ET), multi-level utility mining using utility pattern tree (MU_UP), multi-level utility mining using lexicographic tree (MU_LG) are also analysed. MUMA was compared with MU_ET, MU_UP and MU_LG. The experiments are performed using different datasets like transaction datasets, weblogdatasets, and synthetic datasets.